Fixed Points of L-Fuzzy Mappings in Ordered b-Metric Spaces - Ismat Beg; Mohamed A. Ahmed; Hatem A. Nafadi (Journal of Function Spaces)
We prove common fixed point theorems for weakly commuting and occasionally coincidentally idempotent L-fuzzy mappings in ordered b-metric spaces. We also obtain common fixed point for pair of mapping satisfying (JCLR) property. An application to integral type and usual contractive condition is given.